Evaluation of the Brown Bear Viewing Experience at Katmai National Park and Preserve: Implications for Management. Issue 5 (3rd September 2017) - Skibins, Jeffrey C.; Sharp, Ryan L.
ABSTRACT: Bear experts regularly recommend limiting visitor access to areas critical to bear survival (e.g., feeding grounds). Seeing a bear in the wild, however, is a highly prized visitor experience. This article measured how viewing bears influenced visitors' connection to bears (conservation caring), park interest, and support for restrictive management. Data were obtained from 235 visitors at Katmai National Park and Preserve. Conservation caring and support for restrictive management were consistent until visitors spent 11 hours or more watching bears. Thus, managers may not need to focus on increasing duration of time spent on viewing platforms. Conservation caring predicted levels of park interest (β = .51) and support for restrictive management (β = .44). These data suggested anytime spent watching bears is capable of producing moderate emotional connections and strong support for management. As visitors form an emotional connection to a resource, they are more supportive of stricter management actions.